Kombinasi Ekstrak Bunga Kenanga (Cananga odorata) dan Serai Wangi (Cymbopogon nardus) Terhadap Kematian Nyamuk Aedes sp. - Hazimi Hazimi; Fathmawati Fathmawati; Izzatul Yazidah; Muhammad Pahruddin (Jurnal Skala Kesehatan, 2026)
Ylang ylang flower plants (Cananga odorata) and citronella (Cymbopogon nardus) have potential as plants capable of killing Aedes sp. mosquitoes. This study aims to analyze the effectiveness of combined concentrations of ylang ylang flower extract (Cananga odorata) and citronella (Cymbopogon nardus) on mortality. Aedes sp. mosquitoes. The method used was a quasi-experimental (Quasi Experiment Design), where a combination of ylang-ylang flower extract and citronella extract with a concentration of 2%, 4%, 6%, 8% and 10% were sprayed on mosquitoes and then observed for 24 hours. Analysis of this research data was done using One Way Anova and Post hoc to see the differences between concentrations, then a probit analysis was carried out to see the LC50. The results showed that the 10% concentration of the combination of ylang-ylang flower extract and citronella showed a difference from the control, the LC50 value after 24 hours of contact was 16.76%. The conclusion from the research results is that the combination of ylang ylang flower extract (Cananga Odorata) and citronella (Cymbopogon Nardus) is effective in killing Aedes sp mosquitoes. with a concentration of 16.76%. It is recommended for future researchers to increase the concentration and range between concentrations.